Diffuse cutaneous dermographic mastocytosis. - Garofalo, L. (European Journal of Pediatric Dermatology, 2016)
The most common form of mastocytosis in children is urticaria pigmentosa, of which there is a macular and a maculopapular variant; the second more frequent form is nodular mastocytoma with one or even with more elements (1). Both in the papular variant of urticaria pigmentosa and more easily in mastocytoma bullous lesions representing an exaggeration of urticarial-like lesions may occur from time to time. The rarest form is diffuse cutaneous mastocytosis where the skin is diffusely infiltrated by mast cells and assumes a doughy or leather-like consistency; the diffuse infiltration may be associated with exudative bullous or vesicular lesions, marked dermographism, persistent pitting and aged appearance. A sallow, xantelasmoid discoloration may be present both in the papular-nodular form and diffuse form. The systemic form in the child is exceptionally rare (2).